Characterization of carbonaceous matter emitted from residential coal and biomass combustion by experimental simulation. (15th January 2023) - Cui, Min; Xu, Yuanyuan; Yu, Binbin; Yan, Caiqing; Li, Jun; Zheng, Mei; Chen, Yingjun
Abstract: The characteristics of the carbon components emitted during coal and biomass combustion changed sharply, owing to rapid and increasingly complex combustion conditions and changes in fuel variety. However, comprehensive experiments on the various factors influencing the characteristics of carbonaceous substance emissions from residential fuel combustion are severely lacking, which makes it difficult to compile accurate emission inventories and source apportionment. In this study, ten types of coal and eight types of biomass burned in a muffle furnace at different combustion temperatures were used to determine the emission characteristics of carbonaceous substances. The ranges of emission factors (EFs) of fine particulate matter (PM2.5 ), organic carbon (OC), elemental carbon (EC) and a total of 16 United States Environmental Protection Agency (EPA) priority control polycyclic aromatic hydrocarbons (PAHs) ranged from 1.96 to 17.75, 0.83 to 10.97, 0.14 to 1.19 and 0.017 ± 0.01 to 0.009 ± 0.007 g/kg for coal combustion, and 2.44 to 17.7, 1.07 to 9.34, 0.3 to 1.66 and 0.016 ± 0.02 to 0.18 ± 0.30 g/kg for biomass burning, respectively. Combustion temperature and fuel type were important factors affecting carbonaceous substance emissions. The mean EF PM 2.5, EFOC for residential fuel, and EFPAHs for coal combustion were significantly greater at lower temperatures than at higher temperatures; however, the trends for mean EFEC for residential fuel and EFPAHs for biomass were opposite. The emission characteristics of PM2.5, OC, EC, and PAHs for coals of varying maturity were different at low and high combustion temperatures, which might indicate that coal maturity was a main influencing factor at low combustion temperatures, whereas other factors were dominant at high combustion temperatures. Finally, the PAHs diagnostic ratios were discussed and found to be inconsistent with previous studies for some conditions, which indicated that they should be used cautiously for source apportionment studies. Graphical abstract: Image 1 Highlights: Comprehensive emission factors of carbonaceous matters were obtained. Emission factors of carbonaceous matters were affected highly by temperature and fuel types. Different species formation mechanisms were changed on different temperature.